The Implementation of Regional Policy in Lithuania - Ragauskienė, Erika (Ekonomika, 2005)
There are two types of regional policy - EU regional policy and national (state) regional policyin place in Lithuania. The common goal of these policies is the same - social and economic cohesion, however, in an EU context, Lithuania is regarded as a single region, while the focus of national regional policy is to address the interregional social and economic imbalances in Lithuania. To achieve balanced development as much in Lithuania as a whole as in its regions, the co-ordinated implementation of both policies is very important. The aim of this article is to analyse EU regional policy. as well as the effect of EU structural funds on regional policy in Lithuania, and in this way to highlight the problem of unequal regional social and economic development. Particular attention is given to the provisions of Lithuanian regional policy and the mechanisms of its implementation.Research aims. To analyse EU regional policy as well as the effect of EU structural assistance on variations in Lithuanian regional policy. highlighting the most important contributing factors. Research object. Lithuanian regional policy and EU structural assistance. Research methods and resources. The following research methods were used: an analysis of academic literature; information comparison, grouping, elaboration and summation, data analysis techniques. Resources used include academic literature, EU regulations, normative acts of the Republic of Lithuania regulating regional policy and the use of structural funds, and data from the Department of Statistics to the Government of the Republic of Lithuania and the Ministry of Finance.